Performance measurement and management in portuguese law enforcement - Gomes, Patrícia S. (2013)
Performance measurement of police services is complicated by ambiguous and complex goal- and objectives-setting, and by the difficulties of measuring outputs. This article looks at the organizational and management changes being made in Portuguese police forces. The authors fill a gap in the literature on performance measurement in Portugal by taking a national approach to the study of how law enforcement agencies are introducing new management accounting changes. The article therefore widens the debate on performance measurement and performance improvements in law enforcement.